Waiting for "Superman" [videorecording (DVD)] - Guggenheim, Davis; Strickland, Bill; Canada, Geoffrey; Rhee, Michelle; Weingarten, Randi (Paramount Home Entertainment, 2011)
Provided is an engaging and inspiring look at public education in the United States. This documentary has helped launch a movement to achieve a real and lasting change through the compelling stories of five unforgettable students such as Emily, a Silicon Valley eighth-grader who is afraid of being labeled as unfit for college, and Francisco, a Bronx first-grader whose mom will do anything to give him a shot at a better life. Included are featurettes, and commentary.